2010
DOI: 10.1111/j.1601-0825.2010.01704.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptide hCAP‐18/LL‐37 protein and mRNA expressions in different periodontal diseases

Abstract: hCAP-18/LL-37 has an important role in innate response during periodontal inflammation. Local deficiency in hCAP-18/LL-37 might be a confounding effect in the pathogenesis of generalized aggressive periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…Furthermore, findings from some in vivo studies have demonstrated that LL-37 is usually associated with periodontal disease, a common oral inflammatory disorder [7,8,9]. For example, the levels of mRNA expression coding for hCAP-18 in tissue samples with chronic periodontitis appear to be upregulated compared with healthy control tissue [8]. Likewise, the levels of LL-37 are elevated in GCF of patients with chronic periodontitis [6,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, findings from some in vivo studies have demonstrated that LL-37 is usually associated with periodontal disease, a common oral inflammatory disorder [7,8,9]. For example, the levels of mRNA expression coding for hCAP-18 in tissue samples with chronic periodontitis appear to be upregulated compared with healthy control tissue [8]. Likewise, the levels of LL-37 are elevated in GCF of patients with chronic periodontitis [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…The levels of LL-37, derived from hCAP-18 by proteolytic cleavage, are also detectable in saliva [5] and gingival crevicular fluid (GCF) [6]. Furthermore, findings from some in vivo studies have demonstrated that LL-37 is usually associated with periodontal disease, a common oral inflammatory disorder [7,8,9]. For example, the levels of mRNA expression coding for hCAP-18 in tissue samples with chronic periodontitis appear to be upregulated compared with healthy control tissue [8].…”
Section: Introductionmentioning
confidence: 99%
“…The levels of AMPs in GCF are thought to be associated with periodontal disease, as demonstrated by Puklo et al that the GCF HNP1-3 levels were higher in patients with aggressive or chronic periodontitis when compared to healthy controls (Puklo, Guentsch et al 2008). Gingival tissue samples from chronic periodontitis patients showed elevated mRNA expression and higher immunostaining of LL-37 on neutrophils, while the LL-37 levels were also elevated in the GCF of periodontitis patients (Hosokawa, Hosokawa et al 2006;Turkoglu, Emingil et al 2009;Turkoglu, Kandiloglu et al 2011). In addition, patients with morbus Kostmann syndrome, an inherited disorder that causes lower than normal levels of neutrophils, have been found to be more susceptible to periodontal disease, while those with a bone marrow transplant are not (Putsep, Carlsson et al 2002).…”
Section: Differential Expression Of Amps In Periodontal Health and DImentioning
confidence: 89%
“…After controlling infl ammation with non-surgical debridement, a 16 % decrease in gingival pocket fl uid fl ow and a slightly reduced level of 9 % in the drug level were observed, and these were statistically signifi cant. The infl ammation that occurred in soft tissue compromised the immunological balance and cellular infi ltration rate in both epithelium and connective tissue compared with healthy sites (19) .…”
Section: Discussionmentioning
confidence: 99%